Who decides states as laboratories of constitutional experimentation - Sutton, Jeffrey S. (Jeffrey Stuart) 1960- (Oxford University Press, 2021)
51 Imperfect Solutions told stories about specific state and federal individual constitutional rights, and explained two benefits of American federalism: how two sources of constitutional protection for liberty and property rights could be valuable to individual freedom and how the state courts could be useful laboratories of innovation when it comes to the development of national constitutional rights. This book tells the other half of the story. Instead of focusing on state constitutional individual rights, this book takes on state constitutional structure. Everything in law and politics, including individual rights, comes back to divisions of power and the evergreen question: Who decides? The goal of this book is to tell the structure side of the story and to identify the shifting balances of power revealed when one accounts for American constitutional law as opposed to just federal constitutional law. The book contains three main parts-on the judicial, executive, and legislative branches-as well as stand-alone chapters on home-rule issues raised by local governments and the benefits and burdens raised by the ease of amending state constitutions. A theme in the book is the increasingly stark divide between the ever-more democratic nature of state governments and the ever-less democratic nature of the federal government over time"--